Strategi Pengembangan Keuangan dan Pemasaran pada UMKM Medokan Semampir Surabaya - Shanti Shanti; Maria Mia Kristanti; Ani Suhartatik (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
This community service (Abdimas) activity was carried out in response to the needs of MSMEs Medokan Semampir Surabaya regarding assistance with MSMEs development strategies of financing and marketing. The aim of this Abdimas activity is to provide solutions to problems of development strategies in the financing and marketing. This Abdimas activity is carried out through sharing, discussion, and tutorial/mentoring methods. The results of this Abdimas activity show that the majority of MSMEs have not carried out financial reporting in accordance with generally accepted EMKMs standards and market their products manually. It is hoped this Abdimas activity can be solutions to the problems faced by MSMEs, so that they can progress sustainably.